الجزائريون المسلمون والبلديات المختلطة 1847-1884 - زقب, عثمان (جامعة الوادي - University of Eloued, 2022)
إن أهداف الإدارة الاستعمارية في فرض النظام المدني، وتوسيع دائرته كانت مكشوفة من السياسات المطبقة؛ والمدعومة أساسا من كتلة المعمرين؛ في مواجهة ما يعتبرونه حكم عسكري قمعي. إن هذه المطالب في الواقع كانت تخفي الوجه البشع للمعمرين وإدارة الاحتلال في استغلال النظام المدني خاصة البلديات المختلطة، كأداة فعّالة لتحقيق هدفين أساسيين هما: تحقيق التوسع والاستغلال الاستعماري في مناطق الجزائريين المسلمين، وكذا استنزاف مواردهم المالية. تتمثل أهمية هذه الدراسة في الكشف عن كيفية تحول نظام البلديات المختلطة في الجزائر خلال الاحتلال الفرنسي من أداة اختراق واستيعاب للمجتمع الجزائري إلى وسيلة ابتزاز واستثمار في مواردهم المالية لصالح جشع المعمرين وتوسع المشروع الاستعماري في الجزائر. أما أهداف هذه الدراسة فيمكن حصرها في إبراز الدور الخطير الاستغلالي الذي لعبته إدارة البلديات المختلطة بحق الجزائريين المسلمين، ودورها في تكريس سياسة تمييزية عمّقت الفجوة في الحقوق والمنافع بينهم وبين المعمّرين الأوروبيين؛ الذين استخدموا مختلف وسائل الضغط في الجزائر والميتربول من أجل تمرير قوانين وتشريعات ملائمة لمصالحهم المتزايدة. The objectives of the colonial administration in imposing civil order and expanding its circle were exposed from the applied policies; It is supported mainly by the centenarian bloc; in the face of what they see as repressive military rule.the occupation administration in exploiting the civil system, especially the mixed municipalities, as an effective tool to achieve two main goals: achieving expansion and colonial exploitation in the areas of Algerian Muslims, as well as depleting their financial resources. The importance of this study is to reveal how the system of mixed municipalities in Algeria was transformed during the French occupation from a tool of penetration and absorption of Algerian society into a means of extortion and investment in their financial resources in favor of the greed of the centenarians and the expansion of the colonial project in Algeria. As for the objectives of this study, they can be limited to highlighting the dangerous and exploitative role played by the administration of mixed municipalities against Algerian Muslims, and its role in perpetuating a discriminatory policy that deepened the gap in rights and benefits between them and the European centenarians. Who used various means of pressure in Algeria and Metropol in order to pass laws and legislation appropriate to their growing interests. In fact, these demands were hiding the ugly face of the centenarians and
مقال
Keywords: البلديات ; الاحتلال ; الإدارة ; المختلطة ; الاستغلال; Municipalities; Occupation; Administration; Mixed; Exploitation